Enhancing Students’ Engagement, Self-Efficacy, and Mathematics Concept Mastery Through the Implementation of the Flipped Classroom Model at Quiver Center Academy : [Peningkatan Keterlibatan Siswa, Efikasi Diri, dan Penguasaan Konsep Matematika Melalui Penerapan Model Kelas Terbalik di Quiver Center Academy] - Gillian Tampi (Universitas Pelita Harapan, 2024)
The COVID-19 pandemic has caused significant disruption in the education sector, forcing schools to shift their learning processes to online platforms. This transition to online learning is widely regarded as the most viable option for distance education. The present research was motivated by observed issues in Grade ten Mathematics, specifically passive student engagement, low self-efficacy, and poor concept mastery during classes conducted via video conferencing. The aim of this study was to improve students' engagement, self-efficacy, and concept mastery in Mathematics through the implementation of the Flipped Classroom Model during the pandemic. This Classroom Action Research was carried out over three learning cycles, with the subjects consisting of five Grade ten students from Quiver Center Academy. Data were collected through observations, surveys, and test assessments. The analysis of data from the three cycles indicated a twenty-nine percent increase in student engagement, a fifty-five percent increase in academic self-efficacy, and a sixteen percent improvement in concept mastery. In conclusion, the implementation of the Flipped Classroom Model effectively enhanced student engagement, self-efficacy, and concept mastery in grade ten Mathematics at Quiver Center Academy.